INVESTIGATING GRAMMATICAL INTERFERENCE IN JUNIOR HIGH SCHOOL STUDENTS' TRANSLATION - Riyanda, Wahyu Budi (2015)
This study is conducted to investigate grammatical interference that junior high school students encounter using Indonesia-English translation. The study uses descriptive-qualitative design, using error analysis as the tool of data analysis. The study is conducted in a public junior high school in Bandung with 36 eight graders as the participants. The main data of this study are collected from three times in-class observation, the students' Indonesia-English translations and interview. The findings reveal that the most frequent grammatical interference that is experienced by the students is the absence of morpheme "s" in plural forms. The probable factor that contributes to its occurrence is the non-existence of English interaction which is evident through classroom observation. In addition, the students also confess their difficulties in learning English which are memorizing verb changes (tense), pronunciation, memorizing vocabulary and lack of motivation to communicate in English. Keywords: Second Language Acquisition, Negative Language Transfer, Grammatical Interference   Penelitian ini dilaksanakan untuk menginvestigasi Grammatical Interference yang dialami siswa sekolah menengah pertama dengan menggunakan terjemahan Indonesia-Inggris. Desain penelitian ini adalah kualitatif-deskriptif, menggunakan Error Analysis sebagai alat analisis data. Penelitian ini dilaksanakan di salah satu sekolah menengah pertama di Bandung dengan partisipan sebanyak 36 siswa kelas delapan. Data utama dari penelitian ini diperoleh dari tiga kali observasi dalam kelas, terjemahan Indonesia-Inggris dari siswa, dan wawancara. Hasil dari penelitian ini menunjukkan bahwa Grammatical Interference yang paling sering dialami oleh siswa adalah ketiadaan morfim "s" dalam bentuk jamak. Faktor yang memungkinkan munculnya Grammatical Interference tersebut adalah tidak adanya interaksi menggunakan Bahasa Inggris di dalam kelas yang terlihat dalam observasi kelas. Siswa-siswa di dalam penelitian ini juga menyampaikan bahwa mereka memiliki kesulitan dalam mempelajari Bahasa Inggris yaitu menghafal perubahan kata kerja (Tense), pengucapan, menghafal kosa kata, dan kurang motivasi untuk berkomunikasi menggunakan Bahasa Inggris. Kata Kunci: Penguasaan Bahasa Kedua, Transfer Negatif Bahasa, Grammatical Interference